PENGENALAN PEMROGRAMAN UNTUK SISWA PAKET C PKBM AL-HAMRA (CODING FOR KIDS) - kurniawan, yudi; Ardhiansyah, Maulana; Nurjaya, Nurjaya (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The rapid development and progress of information technology has a negative impact on students, namely the portion of time between doing assignments and playing games, so The portion of time spent playing games is much longer than the portion of time spent doing assignments, so that in the end, students play games more than doing assignments, In fact, many students become addicted to playing games, thereby reducing students' productivity, interaction and moral discipline. Seeing this phenomenon, the Ministry of Communication and Informatics designed and implemented digital literacy activities considering the importance of accelerating digital transformation, one of which is by supporting activities to introduce programming or coding for children, which aims to increase children's competence from their hobby of playing with gadgets so that they can be directed gradually so that children don't just use gadgets or play games but can produce games. It needs to be realized that the rapid development of information technology not only has a positive impact and great opportunities but also requires every country in the world to create quality human resources, one of which is by improving the quality of education by developing character through IT learning. Introducing and teaching coding to children has many benefits, especially if taught from an early age. Learning coding from an early age can make people who learn have a disciplined and thorough nature and can help them solve problems they face later Keywords: Information Technology, Students, Introduction to Programming Languages